KAJIAN USAHATANI SAYURAN BANTARAN SUNGAI BARABAI PASCA BANJIR DI KABUPATEN HULU SUNGAI TENGAH - Fitri Mahyudi; Husinsyah Husinsyah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2021)
This Research aim to know technically about Vegetables Farming Study of Barabai Riverbank Post The Flood In Hulu Sungai tengah District and to know”about”cost, acceptance, ”revenue and vegetables farming Feasibility. Pursuant to result of seen from technical management vegetables farming still relative modestly, this seen from farm processing until the conservancy. Tomato Net Profit obtained from 32 vegetables farmer in Alat village and 27 vegetables farmer in Datar Ajab village responder with wide mean equal to Rp. 5.594.002,34/farmer and Chili Net Profit with wide mean equal to Rp. 6.919.998,88.002,34/farmer. RCR Value Tomato farming 1.15 and RCR Value Chili farming 1.20 competent so that to be feasible (RCR >1)